Improving the Quality of Education of Students through Tutoring in Karangmulyo Village, Pegandon Subdistrict, Kendal Regency - Wiwit Yuliani; Desti Pamungkas; Kautsar Rizky Mahardika; Eva Maulidya; Muhammad Faiz Wibowo (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
Quality education is an essential transformation tool that measures the progress of a nation and shapes competent human resources. However, the education system faces various challenges caused by budget limitations, unequal access, and the influence of the social environment that occurs in some areas. This research focuses on the tutoring program “Les Cemara” in Karangmulyo Village, Pegandon, Kendal, which aims to improve the quality of education of elementary school children through tutoring in English and mathematics. The research method used is descriptive qualitative with a teaching method using Jean Piaget's theory, namely mentoring. The basic principles of Piaget's theory such as schema, assimilation, accommodation, and equilibration are used to analyze how children acquire knowledge and develop their skills. The results show that the program can improve children's motivation to learn and the quality of their education. The use of Piaget's approach allows children to learn through active interaction and direct experience.